Strategy Implementation in Efforts to Improve Teacher Performance - Sartika, Dwi; Mulyono, Sugeng; Nasir, M. Jamal Abdul (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to identify the application of strategies to improve teacher performance. The research focus was on Tahfidz Elementary School teachers in Lumajang, especially Tahfidz Al Aziz Elementary School, Bahrusysyifa Qur'an Elementary School, and Cahaya Qur'an SQS. This research uses a qualitative approach. Research data was obtained from informants, including school principals, teachers and student guardians. Data collection methods include observation, interviews, and documentation. Data were analyzed inductively using data reduction steps, data presentation and conclusion. The findings of this research indicate that the implementation of strategies in an effort to improve teacher performance is improving performance by building intense communication between school principals and teachers, holding independent coaching, conducting evaluation meetings, attending official education and training, holding comparative studies, and fulfilling teacher welfare.